Clinical Pharmacology & Therapeutics: The Next Five Years - Waldman, SA (Clin Pharmacol Ther, 2014)
It has been nearly ten years since we joined the editorial organization of Clinical Pharmacology & Therapeutics (CPT), as part of the American Society for Clinical Pharmacology and Therapeutics (ASCPT) family. During that tenure, the primary mandate has been the growth of CPT, recognized as one of the key voices of the discipline and the Society. Set goals were realized in concert with a strong editorial team, a diverse editorial board, a dedicated editorial staff, and outstanding authors, leveraging a leading publishing infrastructure and responding to the needs of a global readership, expanding membership, and the discipline as a whole. The impending decade anniversary, and the transition to a new publisher, offers a natural juncture to reflect on progress, and chart plans for the future of the Journal.